The Analyzing of Anonymous Trolling Comment On Social Media - fera Indasari; Siti Anisyah; Sepriadi Saputra (Jurnal Studi Sosial dan Politik, 2024)
In this digital era, social media has become a space for interaction and communication for most people. However, behind its convenience and benefits, social media is also a place for negative behavior to emerge. One phenomenon of provocative comments on social media that often appears on social media platforms is trolling. This research aims to understand " Anonymous Trolling Comments in Social Media". This research uses a literature review study method for literature searches using internet sources. First, researchers understand and describe the negative impact of trolling comments on the use of social media. The analysis results reveal that Trolling comments have a bad psychological impact on the message recipients. Anonymity can give trolls the freedom to make negative, provocative, or irrelevant comments without fear of consequences. With anonymity, one can avoid the threat of social influence such as hostility between groups, violent consequences, etc. Victims of trolling often feel personally attacked, insulted, and degraded. There needs to be outreach to the public to overcome trolling comments that occur so that the negative impact of trolling comments can be minimized.